The cost of electricity interruption for manufacturing firms in Ethiopia: Valuing outage by applying stated preference approach - Birku Reta Entele; Shibiru Ayalew (Journal of Applied Economics, 2024)
In sub-Saharan African countries, firms are suffering from frequent, long-lasting and random power outage, which makes planning and production activities difficult. Thus, understanding a firm's cost associated with unreliable power supply is crucial for policymakers and potential investors in the energy sector. To this end, we estimated the economic cost of power interruption to manufacturing firms in selected cities of Oromia Regional State in Ethiopia using a mixed logit model. We collected data from a sample of 600 manufacturing firms. The result shows that a firm's average cost of power interruption is equivalent to ETB 51,777 ( US976) per month, which corresponds to a nine-fold of their current monthly electricity bill. In addition, the interruption costs amount to 2.22% of a firm's gross monthly revenue. Moreover, we observed a considerable variation in our results, which be partly attributed to company size and type of industry where a company belongs to.
Keywords: 330; Economic cost; Ethiopia; manufacturing firms; power interruption